Prokaryotic maintenance respiration and growth efficiency field patterns reproduced by temperature and nutrient control at mesocosm scale. (28th December 2022) - Verma, Ashish; Amnebrink, Dennis; Pinhassi, Jarone; Wikner, Johan
Abstract: The distribution of prokaryotic metabolism between maintenance and growth activities has a profound impact on the transformation of carbon substrates to either biomass or CO2 . Knowledge of key factors influencing prokaryotic maintenance respiration is, however, highly limited. This mesocosm study validated the significance of prokaryotic maintenance respiration by mimicking temperature and nutrients within levels representative of winter and summer conditions. A global range of growth efficiencies (0.05–0.57) and specific growth rates (0.06–2.7 d −1 ) were obtained. The field pattern of cell‐specific respiration versus specific growth rate and the global relationship between growth efficiency and growth rate were reproduced. Maintenance respiration accounted for 75% and 15% of prokaryotic respiration corresponding to winter and summer conditions, respectively. Temperature and nutrients showed independent positive effects for all prokaryotic variables except abundance and cell‐specific respiration. All treatments resulted in different taxonomic diversity, with specific populations of amplicon sequence variants associated with either maintenance or growth conditions. These results validate a significant relationship between specific growth and respiration rate under productive conditions and show that elevated prokaryotic maintenance respiration can occur under cold and oligotrophic conditions. The experimental design provides a tool for further study of prokaryotic energy metabolism under realistic conditions at the mesocosm scale.